INVESTIGATION OF TURN-TO-TURN CONTACT RESISTANCES OF LARGE-SCALE D-SHAPED NO-INSULATION HIGH-TEMEPERATURE SUPERCONDUCTING MAGNETS TO ACHIEVE SHORT CHARGNING DELAY AND HIGH THERMAL STABILITY (ETIMA, 2024)
To generate ultra-high magnetic fields, a no-insulation (NI) winding technique was proposed by Hahn on 2011. By removing insulators between turns, the NI winding technique enables a high-temperature superconducting (HTS) magnets to improve the thermal stability while generating ultra-high magnetic fields. The NI winding technique has commonly been applied to circular coils for the targets of magnetic resonance imaging (MRI), nuclear magnetic resonance (NMR), air-core cyclotron called as skeleton cyclotron, and so on. Recently, meterclass (large-size) D-shaped NI HTS magnets used for compact fusion reactors are under development applying the NI winding technique. One of critical issues is that large-size D-shaped NI magnets have a long excitation delay. High turn-to-turn contact resistances on NI HTS coils shorten the charging delay times, although high turn-to-turn contact resistances deteriorate the thermal stability. Therefore, the relation between the excitation delay and the thermal stability was investigated on different turn-to-turn contact resistances. Finally, we could find the appreciate resistances with the short charging time and the high thermal stability for two different sizes of D-shaped NI HTS coils.
Keywords: High-temperature superconducting magnets; no-insulation winding technique; thermal stability; excitation delay; D-shaped coil